2021
DOI: 10.3390/medicina57060535
|View full text |Cite
|
Sign up to set email alerts
|

Cataract Development by Exposure to Ultraviolet and Blue Visible Light in Porcine Lenses

Abstract: Background and Objectives: Cataract is still the leading cause of blindness. Its development is well researched for UV radiation. Modern light sources like LEDs and displays tend to emit blue light. The effect of blue light on the retina is called blue light hazard and is studied extensively. However, its impact on the lens is not investigated so far. Aim: Investigation of the impact of the blue visible light in porcine lens compared to UVA and UVB radiation. Materials and Methods: In this ex-vivo experiment, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 45 publications
1
16
0
Order By: Relevance
“…The effect of blue light on the retina is called blue light hazard and is studied extensively. In an animal model, all investigated irradiation sources cause cataracts in porcine lenses-even blue visible light ( 45 ). There is a sense in which electronics are more convenient than books in effective online learning and ensure that the contents of the courses meet the educational requirements.…”
Section: Possible Effects Of Web-based Online Learning On Visual Functionmentioning
confidence: 99%
“…The effect of blue light on the retina is called blue light hazard and is studied extensively. In an animal model, all investigated irradiation sources cause cataracts in porcine lenses-even blue visible light ( 45 ). There is a sense in which electronics are more convenient than books in effective online learning and ensure that the contents of the courses meet the educational requirements.…”
Section: Possible Effects Of Web-based Online Learning On Visual Functionmentioning
confidence: 99%
“…These methods allow a comparison of the opacity of lenses before and after irradiation with different wavelengths. For visualizing cataract in the porcine lenses a single lens is placed in a Petri dish with a mounting disk that prevents the lens from sliding around, which is filled with BSS and a picture is taken with a dark field microscope [21]. The dark field microscope camera generates a grayscale image.…”
Section: Methodsmentioning
confidence: 99%
“…The influence of conventional light sources such as LEDs or fluorescent tubes emitting blue light has been mainly studied for its impact on the retina but has remained unexplored for the lens. Haag et al reported that blue light with a wavelength of 460 nm has the greatest effect on cataract formation in ex-vivo porcine lenses in comparison to UVA and UVB radiation [21]. Based on these results, this work analyses and compares the impact of further visible wavelengths.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…These risk factors include UVlight exposure, hypertension, diabetes, body mass OPEN ACCESS index (BMI), drugs, nutrition, smoking and socioeconomic status. 4,5 However, the advancement of age, a non-modifiable risk factor, is the single most important reason for Cataract. 6 This progression of age is what leads to Senile Cataract.…”
Section: Introductionmentioning
confidence: 99%